If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-3+9=11
We move all terms to the left:
x-3+9-(11)=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5
| 2(r+8)+5r=-5 | | 2u-32=9(u-9) | | 16.1x^2+20x+300=0 | | 7n+6-4n=-9 | | u+7=30 | | x+.86x=500 | | 2(-3x+2=-38) | | 5x-2=18;4 | | 3+3z=-9+3z | | 15m+5m-4=16 | | 91+43+x=180 | | 3n-3=4n=1 | | 2,8+2,8+x+x=21 | | 8x+3.5=4(3x+1.5)+5x | | 12=k/4+11 | | 2y=0.5+6 | | 99+26+x=180 | | 8+x=13=2x | | 8(1)=-4y=-12 | | 4x-60=x-10 | | X-3(4x+54)=3x-7 | | 16-3p=2/5p+5 | | -5(-x+2)=5x-5 | | -6=-4+2v | | -8a+10=2(5–4a) | | |5x-1|-5=-3 | | 71-2x=86-3x | | 1/2(6-x)+3=1/2x-8 | | 23=3y+8 | | -65.376=7.2(9c+1 | | 3-(x-4)=3+4x | | 1/2(6-x)+3=1/2x=8 |